Retrospective Study of Traumatic Dental Injuries in North-East of Iran - Mahshid Sheikh-Nezami; Majid Akbari; Khosro Shamsian; Samaneh Vasigh; Armita Rouhani (Mashhad University of Medical Sciences, 2014)
Introduction: Traumatic dental injuries (TDI) in children and adolescents are a common dental health problem and the prevalence of these injuries has increased during the past few decades. The aim of this paper was to evaluate the data of the patients with dental trauma in permanent teeth looking for treatment in the Dental Trauma Clinic in the North-east of Iran over 4 years. Methods: During the period April 2008 -March 2012 a total of 341 patients presented with dental trauma in the Dental Trauma Clinic; of these, 323 records had the inclusion criteria for further evaluation. Results: Dental records of 323 patients were analyzed, 727 teeth were affected. The numbers of male and female were 217 and 106, respectively. There was a significant difference between genders (P